2017
DOI: 10.3892/ol.2017.5676
|View full text |Cite
|
Sign up to set email alerts
|

Notch1 targeted regulation of mir-224/LRIG2 signaling for the proliferation and apoptosis of cervical cancer cells

Abstract: In the present study, we explored the participation of Notch1 targeted regulation of mir-224/LRIG2 gene signal pathway in proliferation and apoptosis of cervical cancer cells. Forty-nine cases of cervical cancer lesion samples from cervical cancer patients treated in our hospital from February 2013 to February 2015 were chosen as subjects (the observation group), and cervical samples of healthy women (42 cases) during the same period were used as the control group. We determined the mRNA and protein expression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 16 publications
0
8
0
Order By: Relevance
“…For example, The Notch1 gene is reported to be related to CC as well as promote the occurrence of this disease. The potential mechanism shows that Notch1 regulates the proliferation of CC cells by regulating the mir-224/LRIG2 signal pathway [20]. In addition, sulfiredoxin was demonstrated to be an oncoprotein in CC and promote CC metastasis by activating the Wnt/β-catenin signaling.…”
Section: Discussionmentioning
confidence: 99%
“…For example, The Notch1 gene is reported to be related to CC as well as promote the occurrence of this disease. The potential mechanism shows that Notch1 regulates the proliferation of CC cells by regulating the mir-224/LRIG2 signal pathway [20]. In addition, sulfiredoxin was demonstrated to be an oncoprotein in CC and promote CC metastasis by activating the Wnt/β-catenin signaling.…”
Section: Discussionmentioning
confidence: 99%
“…Notch‐1 signalling participates in tumourigenesis, chemoresistance, cancer cell growth, and metastasis . It is elevated in organ‐specific cancers, including gynaecological malignancies . Accumulating data has suggested that Notch‐1 is implicated in autophagy and plays a critical role in cervical cancer .…”
Section: Discussionmentioning
confidence: 99%
“…In murine natural T‐regulatory cells, Notch‐1 regulated autophagy controls survival and suppressor activity of these cells . Additionally, Cong et al show that Notch‐1 gene expression is significantly higher in patients with cervical cancer lesions than it is in normal humans, and silencing of Notch‐1 suppresses cell growth. Consistent with previous reports, expression of Notch‐1 was higher in cervical cancer cell lines than in the control H8 cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, the molecular mechanisms underlying the development of CC remain poorly understood. Previous studies have demonstrated that aberrant expression of several proteins is associated with the proliferation and apoptosis of CC cell lines (5,6). Therefore, the identification of genetic alterations that may be associated with the progression of CC may provide insights for the development of novel therapeutic strategies.…”
Section: Introductionmentioning
confidence: 99%